EVALUATION OF CHINA’S RURAL AGRICULTURAL DEVELOPMENT RESPONSE TO FOREIGN INTELLIGENT AGRICULTURE EXPERIENCE - An, Y. K.; Rashid, M. F.; Kamarudin, K. H. (Journal of Engineering and Technology (JET), 2025)
China has always prioritized the advancement of agriculture and encouraged agricultural modernization to play a significant role. Intelligent agriculture is a new framework for advancing agricultural modernization. Hence, this paper examines China’s rural agricultural development response to the foreign intelligent agriculture experience regarding agricultural competitiveness and sustainable agricultural development. This paper concludes a comparative literature analysis after reviewing many publications on intelligent agriculture (including Chinese and English literature) and government policies and developments in various countries. The findings highlighted that China's intelligent agriculture growth is starting to show results. However, there are still several issues across the board. For instance, there is a lack of talent, insufficient scale and intensification, lack of specialized agricultural production information, and imperfections in the infrastructure service facilities of intelligent agriculture and the management system of agricultural science and technology innovation. In response to these issues, suggestions were made to cultivate awareness of intelligent agriculture's development and strengthen planning leadership and resource integration. Therefore, this paper examined and drew inspiration from the intelligent agriculture development systems in advanced nations like Europe and the United Kingdom, identified the state-of-the-art and emerging trends in Chinese agriculture, and offered a development framework for advancing intelligent agriculture in China.